Translational research to improve the treatment of severe extremity injuries. Issue 2 (24th January 2014) - Brown, Kate V; Penn-Barwell, J G; Rand, B C; Wenke, J C
Abstract : Objectives: Severe extremity injuries are the most significant injury sustained in combat wounds. Despite optimal clinical management, non-union and infection remain common complications. In a concerted effort to dovetail research efforts, there has been a collaboration between the UK and USA, with British military surgeons conducting translational studies under the auspices of the US Institute of Surgical Research. This paper describes 3 years of work. Methods: A variety of studies were conducted using, and developing, a previously validated rat femur critical-sized defect model. Timing of surgical debridement and irrigation, different types of irrigants and different means of delivery of antibiotic and growth factors for infection control and to promote bone healing were investigated. Results: Early debridement and irrigation were independently shown to reduce infection. Normal saline was the most optimal irrigant, superior to disinfectant solutions. A biodegradable gel demonstrated superior antibiotic delivery capabilities than standard polymethylmethacrylate beads. A polyurethane scaffold was shown to have the ability to deliver both antibiotics and growth factors. Discussion: The importance of early transit times to Role 3 capabilities for definitive surgical care has been underlined. Novel and superior methods of antibiotic and growth factor delivery, compared with current clinical standards of care, have been shown. There is the potential for translation to clinical studies to promote infection control and bone healing in these devastating injuries.